Gypsum-based silicon dioxide aerogel fireproof coating for steel structure
By using gypsum-based silica aerogel in steel structure fire-retardant coatings and adding modified Elostone nanotubes and fibers, the problem of the existing fire-retardant coatings being easily released from toxic gases and coatings in fires is solved, and the problem of easy falling off by realizing the problem of the existing fire-retardant coatings being able to achieve High thermal insulation, fire resistance and mechanical properties of the paint.
Patent Information
- Application Number
- CN202411449028.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing steel structure fire-retardant coatings release toxic gases in fires, and the thick coating type causes the coating to fall off easily, making it difficult to meet higher fire-retardant needs.
The gypsum-based silica aerogel fire-retardant coating is used to improve the thermal insulation, fire resistance and mechanical properties of the coating by adding modified Elosite nanotubes, basalt fibers and polyvinyl alcohol fibers.
It significantly improves the thermal insulation, fire and smoke resistance and mechanical properties of the coating, reduces the self-weight and risk of falling off of the coating, and is environmentally friendly and energy-saving.
Smart Images

Figure BDA0005088524840000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fire retardant coatings, and in particular relates to a gypsum-based silica aerogel fire retardant coating for steel structures. Background Art
[0002] Steel structure is one of the main structural types of modern buildings. It is widely used in large factories, stadiums, super high-rise buildings, bridges, etc. due to its light weight and simple construction. However, steel structure building materials have unavoidable defects in fire prevention. Steel structure has high thermal conductivity and poor fire resistance. Generally, it will lose its bearing function at around 500℃. If a fire occurs, its mechanical properties will drop sharply, and the steel structure will quickly deform, become unstable, or even collapse.
[0003] At present, steel structure fire retardant coatings are divided into two categories, organic expansion type and inorganic non-expansion type. In the early stage of the development of fire retardant coatings, organic expansion type fire retardant coatings were popular because of their good decorative properties and thickness of only 2 to 7 mm; but most organic substances are prone to aging and have poor weather resistance. In addition, the flame retardants contained in organic fire retardant coatings are mostly CNP or CNP-Cl systems, which contain substances such as melamine and chlorinated paraffin. These substances will quickly decompose and generate gases such as NO2, CO and HCl that are harmful to the human body after being exposed to high temperatures. These gases have a suffocating effect. This results in the first exposure of people to toxic gases released by the expansion of fire retardant coatings due to heat during the fire, thereby increasing the number of casualties caused by building fires. Therefore, environmentally friendly inorganic non-expansion type fire retardant coatings are becoming more and more popular.
[0004] Inorganic non-expanding fire retardant coatings are mainly based on gypsum or cement. They have the advantages of low cost and long ultimate fire resistance time, and are the most widely used fire retardant coatings for steel structures. However, compared with intumescent fire retardant coatings, non-expanding fire retardant coatings have a higher dry density and are thickly coated (coating thickness is about 3 cm). The coating has a large deadweight and is easily caused to fall off in impact or collision. Therefore, it is urgent to invent a fire retardant coating that can solve the above problems to meet the higher demands in the field of fire retardant coating technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a gypsum-based silica aerogel fire retardant coating for steel structures.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A gypsum-based silica aerogel fire retardant coating for steel structure is prepared by the following steps:
[0008] A1, stirring desulfurized gypsum, silica aerogel, modified halloysite nanotubes, water and retarder at 1000-1500 rpm for 10-30 min, mixing evenly to obtain a mixture;
[0009] A2. The mixture obtained in step A1 is mixed with reinforcing fibers and a defoaming agent, and mechanically stirred for 0.5-2 hours to obtain a gypsum-based silica aerogel fire retardant coating for a steel structure.
[0010] Furthermore, the raw materials are calculated in parts by weight as follows: 30-60 parts of desulfurized gypsum, 10-20 parts of silica aerogel, 10-30 parts of modified halloysite nanotubes, 2-4 parts of retarder, 20-40 parts of water, 5-10 parts of reinforcing fiber, and 1-3 parts of defoaming agent.
[0011] Furthermore, the retarder is one of sodium polyphosphate, sodium hexametaphosphate, sodium citrate, potassium tartrate and sodium acrylate.
[0012] Furthermore, the reinforcing fibers are basalt fibers and polyvinyl alcohol fibers, and the mass ratio of the two is 1:1.5.
[0013] Furthermore, the defoaming agent is one of polyethylene glycol, polypropylene glycol, and silicone defoaming agent.
[0014] The prepared fire-retardant coating is based on gypsum, which gives the coating good thermal insulation and fire-retardant properties, and is low in price, environmentally friendly and energy-saving; silica aerogel has excellent thermal insulation properties and low thermal conductivity, and the silica aerogel has low mass, which can make the prepared coating lightweight; the basalt fiber in the reinforcing fiber is a green building material with high elastic modulus, high temperature resistance, corrosion resistance, and hydrophilicity, and the polyvinyl alcohol fiber can also enhance the mechanical strength of the coating. The basalt fiber plays a reinforcing role, and the polyvinyl alcohol fiber plays a toughening role, and the two have good adhesion with the gypsum composite material.
[0015] Further, the modified halloysite nanotubes are prepared by the following steps:
[0016] B1. Disperse the halloysite powder in a 2M sulfuric acid solution in a three-necked flask, react at 200 rpm and 80° C. for 4 h under magnetic stirring, place in a centrifuge tube, centrifuge at 5000 pr / min for 5 min, wash the centrifuged product with deionized water and centrifuge again until the pH value of the aqueous solution of the centrifuged product is neutral, freeze-dry, and obtain the cavity expansion halloysite powder; the ratio of the halloysite powder to the sulfuric acid solution is 5 g:100 mL;
[0017] B2, grinding the cavity expansion halloysite powder obtained in step B1, dispersing the ground powder in an ethanol aqueous solution, adding phytic acid dropwise, stirring and mixing, vacuuming for 1 hour, and then centrifuging at a speed of 5000pr / min to obtain a pre-modified halloysite powder; the ratio of the cavity expansion halloysite powder, the ethanol aqueous solution, and the phytic acid is 5g:100mL:3.5g;
[0018] B3, the pre-modified halloysite powder, cupric chloride dihydrate and ethanol aqueous solution obtained in step B1 are mixed, and ultrasonic reaction is carried out at 70°C for 2 hours. After the reaction is completed, the mixture is filtered, washed repeatedly with water and ethanol, and centrifuged, and freeze-dried to obtain modified halloysite nanotubes; the ratio of the pre-modified halloysite powder, cupric chloride dihydrate and ethanol aqueous solution is 5g:12g:100mL;
[0019] When heated, halloysite nanotubes generate water vapor to absorb a large amount of heat and dilute the oxygen concentration to achieve a flame retardant effect. Halloysite nanotubes have a tubular structure that can capture the flammable small molecules produced by the thermal degradation of polymers, absorbing heat and smoke; when the polymer material burns, the halloysite nanotubes can migrate to the surface of the polymer to act as a physical barrier, inhibiting the exchange of oxygen and heat with the external environment, while slowing down the release of harmful substances; in addition, halloysite nanotubes are rich in Al and Si flame retardant elements, so halloysite nanotubes can greatly enhance the flame retardant properties of coatings; In addition, by modifying the halloysite nanotubes, their inner cavity is expanded after acid treatment compared to ordinary halloysite nanotubes, which increases the copper loading capacity. Since copper, as a flame retardant element, has been proven to have excellent smoke suppression effects, the flame retardant properties of the coating are also enhanced. Finally, the six phosphate groups in phytic acid have strong chelating ability and form complexes with metal cations. Phytic acid has an excellent catalytic carbonization effect when polymer materials burn. Therefore, the modified halloysite nanotubes have excellent synergistic flame retardancy, which significantly improves the flame retardant properties of the coating.
[0020] Beneficial effects of the present invention:
[0021] 1. The fire retardant coating is based on gypsum, which gives the coating good thermal insulation and fire retardant properties, and is low in price, environmentally friendly and energy-saving;
[0022] 2. The added silica aerogel further enhances the thermal insulation performance of the coating, and the silica aerogel has low mass, which can make the prepared coating lighter;
[0023] 3. Among the reinforcing fibers added, basalt fiber plays a reinforcing role, and polyvinyl alcohol fiber plays a toughening role. Moreover, the two have good adhesion with gypsum, which greatly improves the mechanical properties of the coating;
[0024] 4. By modifying the halloysite nanotubes, compared with ordinary halloysite nanotubes, it has excellent synergistic flame retardancy and greatly improves the fire and smoke suppression performance of the coating;
[0025] Therefore, the fire retardant coating prepared by the present invention has excellent heat insulation, fire retardancy and smoke suppression and mechanical properties, and is light in weight, and has important application value in the field of fire retardant coating technology. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] Preparation of modified halloysite nanotubes:
[0029] B1. Disperse 5 g of halloysite powder in 100 mL of 2M sulfuric acid solution in a three-necked flask, and react at 80° C. for 4 h at a speed of 200 rpm under magnetic stirring. After the reaction is completed, place the mixture in a centrifuge tube and centrifuge at 5000 pr / min for 5 min. Wash the centrifuged product with deionized water and centrifuge again until the pH value of the aqueous solution of the centrifuged product is neutral, and freeze-dry to obtain the cavity-expanded halloysite powder.
[0030] B2, grinding 5g of the cavity-expanded halloysite powder obtained in step B1, dispersing the ground powder in 100mL of ethanol aqueous solution, and dropping 3.5g of phytic acid, stirring and mixing, vacuuming for 1h, and then centrifuging at a speed of 5000pr / min to obtain pre-modified halloysite powder;
[0031] B3. Mix 5 g of the pre-modified halloysite powder obtained in step B1, 12 g of copper chloride dihydrate and 100 mL of ethanol aqueous solution, and ultrasonically react at 70° C. for 2 h. After the reaction is completed, filter, wash repeatedly with water and ethanol, centrifuge, and freeze-dry to obtain modified halloysite nanotubes.
[0032] Example 2
[0033] Preparation of modified halloysite nanotubes:
[0034] B1. Disperse 10 g of halloysite powder in 200 mL of 2M sulfuric acid solution in a three-necked flask, and react at 80° C. for 4 h at a speed of 200 rpm under magnetic stirring. After the reaction is completed, place the mixture in a centrifuge tube and centrifuge at 5000 pr / min for 5 min. Wash the centrifuged product with deionized water and centrifuge again until the pH value of the aqueous solution of the centrifuged product is neutral, and freeze-dry to obtain the cavity-expanded halloysite powder.
[0035] B2, grinding 10g of the cavity-expanded halloysite powder obtained in step B1, dispersing the ground powder in 100mL of ethanol aqueous solution, and dropping 7g of phytic acid, stirring and mixing, vacuuming for 1h, and then centrifuging at a speed of 5000pr / min to obtain pre-modified halloysite powder;
[0036] B3. Mix 10 g of the pre-modified halloysite powder obtained in step B1, 24 g of copper chloride dihydrate and 200 mL of ethanol aqueous solution, and ultrasonically react at 70° C. for 2 h. After the reaction is completed, filter, wash repeatedly with water and ethanol, centrifuge, and freeze-dry to obtain modified halloysite nanotubes.
[0037] Example 3
[0038] A1, 30 g of desulfurized gypsum, 10 g of silica aerogel, 10 g of modified halloysite nanotubes prepared in Example 1, 20 g of water and 2 g of sodium polyphosphate were stirred at 1000 rpm for 10 min to obtain a mixture;
[0039] A2. The mixture obtained in step A1 was mixed with 5 g of reinforcing fiber (2 g of basalt fiber and 3 g of polyvinyl alcohol fiber) and 1 g of polyethylene glycol defoamer, and mechanically stirred for 0.5 h to obtain a gypsum-based silica aerogel fire retardant coating for steel structure.
[0040] Example 4
[0041] A1, 45g of desulfurized gypsum, 15g of silica aerogel, 20g of modified halloysite nanotubes prepared in Example 2, 30g of water and 3g of sodium hexametaphosphate were stirred at 1250 rpm for 20min to obtain a mixture;
[0042] A2. The mixture obtained in step A1 was mixed with 10 g of reinforcing fiber (4 g of basalt fiber and 6 g of polyvinyl alcohol fiber) and 2 g of polypropylene glycol defoamer, and mechanically stirred for 1 hour to obtain a gypsum-based silica aerogel fire retardant coating for steel structure.
[0043] Example 5
[0044] A1, 60g of desulfurized gypsum, 20g of silica aerogel, 30g of modified halloysite nanotubes prepared in Example 2, 40g of water and 4g of sodium citrate were stirred at 1500 rpm for 30min to obtain a mixture;
[0045] A2. The mixture obtained in step A1 was mixed with 10 g of reinforcing fiber (4 g of basalt fiber and 6 g of polyvinyl alcohol fiber) and 3 g of polypropylene glycol defoamer, and mechanically stirred for 2 h to obtain a gypsum-based silica aerogel fire retardant coating for steel structure.
[0046] Comparative Example 1
[0047] Ordinary halloysite nanotubes of the same mass were used to replace the modified halloysite nanotubes in Example 5, and the remaining steps were the same as in Example 5 to prepare a coating.
[0048] Comparative Example 2
[0049] Use commercially available gypsum-based fire-retardant coatings.
[0050] The coatings of Examples 3-5 and Comparative Examples 1-2 were made into corresponding shapes according to different test standards and subjected to the following performance tests:
[0051] The impact resistance height is measured using the national standard GB / T 1732-1993 "Determination of impact resistance of paint film";
[0052] The thermal conductivity at 160°C is measured using the national standard GB / T 10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Heat Flow Meter Method". The lower the thermal conductivity, the better the thermal insulation performance.
[0053] The national standard GB 14907-2018 "Fire retardant coating for steel structures" is used to determine the dry density and fire resistance time;
[0054] The smoke density is measured using the national standard GB / T 8627-2007 "Test method for smoke density of burning or decomposition of building materials";
[0055] The measured results are shown in the following table:
[0056]
[0057] It can be seen from the above table that the fire retardant coating prepared in the embodiment of the present invention has excellent thermal insulation, fire resistance, smoke suppression and mechanical properties, and is light in weight, and has important application value in the field of fire retardant coating technology.
[0058] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0059] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A gypsum-based silica aerogel fire retardant coating for steel structure, characterized in that: The invention comprises the following raw materials in parts by weight: 30-60 parts of desulfurized gypsum, 10-20 parts of silicon dioxide aerogel, 10-30 parts of modified halloysite nanotubes, 2-4 parts of retarder, 20-40 parts of water, 5-10 parts of reinforcing fiber and 1-3 parts of defoamer.
2. The gypsum-based silica aerogel fire retardant coating for steel structure according to claim 1, characterized in that: The modified halloysite nanotubes are prepared by the following steps: B1. Dispersing the halloysite powder in a sulfuric acid solution, reacting at 80° C. for 4 h under magnetic stirring, centrifuging after the reaction is complete, washing the centrifuged product and centrifuging again until the pH value of the aqueous solution of the centrifuged product is neutral, and freeze-drying to obtain the cavity-expanded halloysite powder; B2, grinding the cavity-expanded halloysite powder obtained in step B1, dispersing the ground powder in an ethanol aqueous solution, adding phytic acid dropwise, stirring and mixing, vacuuming for 1 hour, and then centrifuging to obtain a pre-modified halloysite powder; B3. The pre-modified halloysite powder obtained in step B1, cupric chloride dihydrate and ethanol aqueous solution are mixed, and ultrasonically reacted at 70° C. for 2 h. After the reaction is completed, the mixture is filtered, washed, centrifuged and freeze-dried to obtain modified halloysite nanotubes.
3. The gypsum-based silica aerogel fire retardant coating for steel structure according to claim 2, characterized in that: In step B1, the ratio of the amount of halloysite powder to the amount of sulfuric acid solution is 5 g:100 mL.
4. The gypsum-based silica aerogel fire retardant coating for steel structure according to claim 2, characterized in that: In step B2, the ratio of the amount of halloysite powder, ethanol aqueous solution and phytic acid used for cavity expansion is 5g:100mL:3.5g.
5. The gypsum-based silica aerogel fire retardant coating for steel structure according to claim 2, characterized in that: In step B3, the ratio of the pre-modified halloysite powder, cupric chloride dihydrate, and ethanol aqueous solution is 5 g:12 g:100 mL.
6. The gypsum-based silica aerogel fire retardant coating for steel structure according to claim 1, characterized in that: The retarder is one of sodium polyphosphate, sodium hexametaphosphate, sodium citrate, potassium tartrate and sodium acrylate.
7. The gypsum-based silica aerogel fire retardant coating for steel structure according to claim 1, characterized in that: The reinforcing fibers are basalt fibers and polyvinyl alcohol fibers, and the mass ratio of the two is 1:1.
5.
8. The gypsum-based silica aerogel fire retardant coating for steel structure according to claim 1, characterized in that: The defoaming agent is one of polyethylene glycol, polypropylene glycol and silicone defoaming agent.
Citation Information
Patent Citations
Fiber-modified gypsum-based composite material
CN102503330A
Flame-retardant antibacterial compound containing halloysite, and preparation method thereof
CN110746654A
High-flame-retardant gypsum-based fiberboard and preparation method thereof
CN115959877A
Fireproof thermal insulation coating and application thereof
CN116751471A
Lightweight gypsum-based aerogel fireproof coating for steel structure and preparation method of lightweight gypsum-based aerogel fireproof coating
CN117645807A